Evidence of Non-microtubule Spindle Forces in Mesostoma ehrenbergii Spermatocytes - Fegaras-Arch, Eleni; Berns, Michael; Forer, Arthur (Frontiers in Molecular Biosciences, 2020)
We tested conclusions reached in previous experiments in which Mesostoma spermatocyte chromosomes moved rapidly to a pole in the absence of microtubules: after 10 μM nocodazole (NOC) depolymerized metaphase spindle microtubules, kinetochores from each of the 3 bivalents detached from the same pole and rapidly moved to the other pole, at speeds averaging 37.7 μm/min. with some as high as 100 μm/min. We concluded that these very fast movements were due to non-microtubule forces arising from a spindle matrix. However, since the chromosomes stretch out before detaching, there is tension in the chromosomes from the stretch. Thus the movements of detached kinetochores conceivably might be due to recoil from the tension, though we argued against this possibility (Fegaras and Forer, 2018a). In this article we test whether recoil causes the movements. We cut bivalents into 2 pieces, using a femtosecond laser, before addition of NOC. When 1 bivalent was severed, all kinetochores moved to one pole in 12/15 cells; when 2 bivalents were severed, all kinetochores moved to one pole in 4/6 cells; and when all 3 bivalents were severed all kinetochores moved to one pole in 3/9 cells. The bivalent “halves” moved rapidly, with average speeds of 47 μm/min, velocities that are not significantly different from those in cells without any laser-cut bivalents (p > 0.05). Since kinetochores move at the same speeds whether they are part of bivalents or not, NOC-induced chromosome movements are not due to recoil from tension along the full-length bivalent, strongly supporting the idea that non-microtubule forces move chromosomes in Mesostoma spermatocytes.